2006
DOI: 10.5650/jos.55.563
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Venezuelan Asphaltenes in the Bulk and Dispersed State

Abstract: High oil prices have renewed the interest not only in new sources of energy but also in using more efficiently the available oil reserves, which are mostly of the heavy or bituminous type. Many of the problems associated with processing of heavy crude oils come from asphaltenes, roughly defined as fractions which are soluble in aromatic solvents such as toluene and benzene and insoluble in alkanes such as pentane or heptane (1,2). This scientifically vague definition makes difficult a precise characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 46 publications
3
11
0
Order By: Relevance
“…40 °C. Figure B shows that this is fairly close to positions of broad endothermic peaks, observed by DSC studies of solid asphaltenes in ref (curve 1) and ref (curve 2). A second increase of derivatives in Figure A commences at 70−80 °C and obviously continues beyond 105 °C, the upper boundary of the studied temperature range.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…40 °C. Figure B shows that this is fairly close to positions of broad endothermic peaks, observed by DSC studies of solid asphaltenes in ref (curve 1) and ref (curve 2). A second increase of derivatives in Figure A commences at 70−80 °C and obviously continues beyond 105 °C, the upper boundary of the studied temperature range.…”
Section: Resultssupporting
confidence: 80%
“…Of immediate relevance to conductivity experiments described in this paper are previous studies of microstructural transformations in solid asphaltenes at temperatures below 100−150 °C. These transformations have been revealed by measurements of thermal properties, mainly by differential scanning calorimetry (DSC). Masson et al concluded that solid asphaltenes lack a crystalline phase but have an ordered amorphous phase (mesophase), which is identified by an endotherm at around 50 °C in the DSC heat flow curves. They also identified two overlapping glass transitions in the amorphous domains of asphaltenes, with the prevalent one at 70 °C apparently controlled by interactions, involving oligo-aromatic structures in asphaltenes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the O/W emulsions, the average droplet diameter ranged from 13 to 86 µm, while for the W/O systems ranged from 3 to 9 µm. This result could be due to the increase in the polar group concentration at the interface leads to the reduction of interfacial tension and the formation of W/O emulsions [73,74].…”
Section: Concentration (Mg/l) W/o Emulsion (%) O/w Emulsion (%) Asf12mentioning
confidence: 99%